A randomized trial of obeticholic acid monotherapy in patients with primary biliary cholangitis. Issue 5 (29th January 2018) - Kowdley, Kris V.; Luketic, Velimir; Chapman, Roger; Hirschfield, Gideon M.; Poupon, Raoul; Schramm, Christoph; Vincent, Catherine; Rust, Christian; Parés, Albert; Mason, Andrew; Marschall, Hanns‐Ulrich; Shapiro, David; et al.
Abstract : Obeticholic acid (OCA), a potent farnesoid X receptor agonist, was studied as monotherapy in an international, randomized, double‐blind, placebo‐controlled phase 2 study in patients with primary biliary cholangitis who were then followed for up to 6 years. The goals of the study were to assess the benefit of OCA in the absence of ursodeoxycholic acid, which is relevant for patients who are intolerant of ursodeoxycholic acid and at higher risk of disease progression. Patients were randomized and dosed with placebo (n = 23), OCA 10 mg (n = 20), or OCA 50 mg (n = 16) given as monotherapy once daily for 3 months (1 randomized patient withdrew prior to dosing). The primary endpoint was the percent change in alkaline phosphatase from baseline to the end of the double‐blind phase of the study. Secondary and exploratory endpoints included change from baseline to month 3/early termination in markers of cholestasis, hepatocellular injury, and farnesoid X receptor activation. Efficacy and safety continue to be monitored through an ongoing 6‐year open‐label extension (N = 28). Alkaline phosphatase was reduced in both OCA groups (median% [Q1, Q3], OCA 10 mg −53.9% [−62.5, −29.3], OCA 50 mg −37.2% [−54.8, −24.6]) compared to placebo (−0.8% [−6.4, 8.7]; P < 0.0001) at the end of the study, with similar reductions observed through 6 years of open‐label extension treatment. OCA improved many secondary and exploratory endpoints (including γ‐glutamyl transpeptidase, alanine aminotransferase, conjugated bilirubin, and immunoglobulin M). Pruritus was the most common adverse event; 15% (OCA 10 mg) and 38% (OCA 50 mg) discontinued due to pruritus. Conclusion: OCA monotherapy significantly improved alkaline phosphatase and other biochemical markers predictive of improved long‐term clinical outcomes. Pruritus increased dose‐dependently with OCA treatment. Biochemical improvements were observed through 6 years of open‐label extension treatment. (Hepatology 2018;67:1890‐1902).